TOPONOMY "KOKAND" AND ITS CONCEPTUAL STUDY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the names of the layers that make up the toponymy of the city of Kokand are semantically grouped, some of them are explained.